If x , y , z are real and
4 x 2 + 9 y 2 + 1 6 z 2 − 6 x y − 1 2 y z − 8 x z = 0
then x , y , z are in:
(Choose the option that applies to all solutions.)
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How did u get that?
Rearranging the equation we get, 2 ( 2 x − 3 y ) 2 + 2 ( 2 x − 4 z ) 2 + 2 ( 3 y − 4 z ) 2 = 0
Hence the solution of above equation will be: 2 x = 3 y = 4 z
Therefore x,y,z ⇒ x , 3 2 x , 2 x
Clearly in harmonic progression..
Assume, 2x=a , 3y=b , 4z=c , then, we have [ a 2 + b 2 + c 2 = a b + b c + c a ] and this yields a = b = c .
So, 2x = 3y = 4z ⇒ x = 2 k , y = 3 k , z = 4 k , for any real k .
Cleary,
k
2
,
k
3
,
k
4
are in
AP
⇒
2
k
,
3
k
,
4
k
are in
HP
i.e.,
x, y, z
are in HP.
EXcept for the part where I multiplied the entire equation by 2 and then factorized it...did it the same way!!!
true
assume 2x=a, 3y=b & 4z =c so the equation is a^2 + b^2 + c^2 -ab -bc -ca =0 or (a + b + c) (a^2 + b^2 + c^2 -ab -bc -ca) = 0 or a^3 + b^3 + c^3 - 3abc =0 or a^2/bc + b^2/ca + c^2/ab =3 is a HP
Problem Loading...
Note Loading...
Set Loading...
I solved like this: ( 2 x − 3 y ) 2 = 4 x 2 + 9 y 2 − 1 2 x y ( 2 x − 4 z ) 2 = 4 x 2 + 1 6 z 2 − 1 6 x z ( 3 y − 4 z ) 2 = 9 y 2 + 1 6 z 2 − 2 4 y z
After adding this 3 equations you get:
( 2 x − 3 y ) 2 + ( 2 x − 4 z ) 2 + ( 3 y − 4 z ) 2 = 2 ( 4 x 2 + 9 y 2 + 1 6 z 2 − 6 x y − 1 2 y z − 8 x z )
From this we get:
( 4 x 2 + 9 y 2 + 1 6 z 2 − 6 x y − 1 2 y z − 8 x z ) = 2 1 ( ( 2 x − 3 y ) 2 + ( 2 x − 4 z ) 2 + ( 3 y − 4 z ) 2 )
If ( 4 x 2 + 9 y 2 + 1 6 z 2 − 6 x y − 1 2 y z − 8 x z ) is zero we get:
2 1 ( ( 2 x − 3 y ) 2 + ( 2 x − 4 z ) 2 + ( 3 y − 4 z ) 2 ) =0
This expression is zero only when all summands are zero. And from this we get:
2 x = 3 y = 4 z ⇒ ( x , 3 2 x , 2 1 x ) so this is harmonic progression...